2018
DOI: 10.1080/09540121.2018.1479029
|View full text |Cite
|
Sign up to set email alerts
|

Economic strengthening for HIV prevention and risk reduction: a review of the evidence

Abstract: Household economic strengthening (HES) is increasingly implemented alongside HIV programing to address economic drivers of the epidemic. The evidence base on HES for HIV outcomes is growing, and this evidence review aimed to comprehensively consolidate and synthesize the research linking 15 types of HES interventions with a range of HIV prevention and treatment outcomes. The review was conducted between November 2015 and October 2016 and consisted of an academic database search, citation tracking of relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 82 publications
(94 reference statements)
0
33
0
Order By: Relevance
“…Results for the full review are reported in the first paper in this series (Swann 2018a) including overall study characteristics, PRISMA diagram (see appendix 1) and full evidence map (see appendix 2) (Snilstveit, Vojtkova, Bhavsar, Stevenson, & Gaarder, 2016). UCTs are a common form of social protection that provide basic consumption support to stabilize vulnerable individuals or households.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results for the full review are reported in the first paper in this series (Swann 2018a) including overall study characteristics, PRISMA diagram (see appendix 1) and full evidence map (see appendix 2) (Snilstveit, Vojtkova, Bhavsar, Stevenson, & Gaarder, 2016). UCTs are a common form of social protection that provide basic consumption support to stabilize vulnerable individuals or households.…”
Section: Resultsmentioning
confidence: 99%
“…The study limitations are discussed in greater detail in the first paper in this series (Swann 2018a). They include the introduction of reviewer bias in the inclusion of a quality assessment, which was mitigated through the creation of a structured codebook and using two reviewers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 While existing research suggests that these programs have a positive impact on household and community resilience, there is little research to date that elucidates the causal pathways by which complex, multi-component OVC programs work with local social protection systems to achieve these outcomes. We also have little information on the specific causal pathways associated with ES in contributing to HIV-related outcomes, such as improved perceived health status or retention in HIV prevention or care, across individual and community levels (Swann, 2018). Our research aims to address this gap in the evidence through a qualitative case study to build a causal model mapping the impacts of a USAID program known as Community Care Program (CCP) on OVC households in the community of Mumemo in the Marracuene district of Mozambique.…”
Section: Introductionmentioning
confidence: 99%